2018
DOI: 10.1101/373514
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spectral fingerprints or spectral tilt? Evidence for distinct oscillatory signatures of memory formation

Abstract: Decreases in low frequency power (2-30 Hz) alongside high frequency power increases (>40 Hz) have been demonstrated to predict successful memory formation. Parsimoniously this change in the frequency spectrum can be explained by one factor, a change in the tilt of the power spectrum (from steep to flat) indicating engaged brain regions. A competing view is that the change in the power spectrum contains several distinct brain oscillatory fingerprints, each serving different computations. Here, we contrast these… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 84 publications
(167 reference statements)
2
20
0
Order By: Relevance
“…While these interactions can be spurious and require strict testing for the presence of oscillations above the 1/f background and against null models that preserve autocorrelation[56, 57], a detailed investigation of which of these interactions are changed during IEDs would help further elucidate the neurophysiological processes that they disrupt. Second, opposing changes in high- and low-frequency bands can sometimes be explained by changes in the slope of the 1/f background, rather than changes in each band individually[58]. In studies of neural activation, the slope and power in specific bands are directly and intuitively related, however it is unclear if such a relationship exists for connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…While these interactions can be spurious and require strict testing for the presence of oscillations above the 1/f background and against null models that preserve autocorrelation[56, 57], a detailed investigation of which of these interactions are changed during IEDs would help further elucidate the neurophysiological processes that they disrupt. Second, opposing changes in high- and low-frequency bands can sometimes be explained by changes in the slope of the 1/f background, rather than changes in each band individually[58]. In studies of neural activation, the slope and power in specific bands are directly and intuitively related, however it is unclear if such a relationship exists for connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies performing a different hybrid navigation and memory paradigm have suggested diverse roles for low theta depending on laterality and hippocampal subregion (Miller et al, 2018;Goyal et al, 2020;Herweg et al, 2020). There has been an increasing body of evidence to suggest that low frequency power decrease and high frequency power increase is associated with performance in a variety of tasks, with this "tilt" in the 1/frequency characteristic inherent to human EEG thought to reflect increased regional neural activity (Fellner et al, 2019). However, we found that low and high theta power increases alone after correction for multiple comparisons were associated with task performance, as previously reported in both MEG (Kaplan et al, 2012) and intracranial EEG (Miller et al, 2018) studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although a useful paradigm, the SME is not a direct test that theta specifically supports the formation or retrieval of associations between items in memory, i.e., a cognitive map of recently acquired information. Moreover, many similar studies report the opposite effect: a hippocampal or cortical decrease in theta power during successful encoding or retrieval (33)(34)(35)(36)(37)(38). These conflicting findings raise serious questions about whether the neural processing of spatial and episodic information relies on the same theta-based mechanisms.…”
Section: Significancementioning
confidence: 99%